Analyzing Risk Determinants in Banks: An Empirical Investigation from UK - ZOU, YINAN (2013)
In order to maintain stable and successful run of the business operations and maximize shareholder value through the trade-off between risk and return, banks should manage multiple types of risks appropriately. This study seeks to investigate specific determinants of credit risk and liquidity risk of banks in United Kingdom (UK). For this purpose, two models are built, in which these two types of risks are employed as dependent variables respectively while bank size, capital (measured by equity to assets ratio) are used as independent variables. In addition, GDP acts as a control variable. All the estimates in this study indicate that bank size has significant negative effects on both credit risk and liquidity risk of UK banks. Equity to assets ratio, which used to measure capital structure of firms, is significantly negatively related with credit risks of banks in UK in the preferred instrumental variable (IV) estimates while has no significant relation with liquidity risk of banks in all the estimates. Finally, GDP negatively affects banks’ liquidity risk in all the estimates while has fairly significant and negative influence on credit risk of banks under the preferred IV model.